The epidemiology of tuberculosis in health care workers in South Africa: a systematic review. Issue 1 (December 2016) - Grobler, Liesl; Mehtar, Shaheen; Dheda, Keertan; Adams, Shahieda; Babatunde, Sanni; Walt, Martie; Osman, Muhammad
Abstract Background In South Africa, workplace acquired tuberculosis (TB) is a significant occupational problem among health care workers. In order to manage the problem effectively it is important to know the burden of TB in health care workers. This systematic review describes the epidemiology of TB in South African health care workers. Methods A comprehensive search of electronic databases [MEDLINE, EMBASE, Web of Science (Social Sciences Citation Index/Science Citation Index), Cochrane Library (including CENTRAL register of Controlled Trials), CINAHL and WHO International Clinical Trials Registry Platform (ICTRP)] was conducted up to April 2015 for studies reporting on any aspect of TB epidemiology in health care workers in South Africa. Results Of the 16 studies included in the review, ten studies reported on incidence of active TB disease in health care workers, two report on the prevalence of active TB disease, two report on the incidence of latent TB infection, three report on the prevalence of latent TB infection and four studies report on the number of TB cases in health care workers in various health care facilities in South Africa. Five studies provide information on risk factors for TB in health care workers. All of the included studies were conducted in publicly funded health care facilities; predominately located in KwaZulu-Natal and Western Cape provinces. The majority of the studies reflect a higher incidence and prevalence of active TB disease in health care workers, including drug-resistant TB, compared to the surrounding community or general population. Conclusions There is relatively little research on the epidemiology of TB in health care workers in South Africa, despite the importance of the issue. To determine the true extent of the TB epidemic in health care workers, regular screening for TB disease should be conducted on all health care workers in all health care facilities, but future research is required to investigate the optimal approach to TB screening in health care workers in South Africa. The evidence base shows a high burden of both active and latent TB in health care workers in South Africa necessitating an urgent need to improve existing TB infection, prevention and control measures in South African health care facilities.